HUMANITARIAN CRISIS AND GLOBAL SOLIDARITY: A STUDY OF THE ROLE OF CIVIL SOCIETY IN RESPONDING TO INTERNATIONAL CONFLICTS - Nurlaili, Leli (Advances In Social Humanities Research, 2023)
The increase in international conflicts in the last two decades has exacerbated humanitarian crises in various parts of the world. While the response of countries and international organizations is often hampered by political interests, civil society actually appears as an important actor in responding to crises and building global solidarity. This research aims to analyze the role of civil society in responding to humanitarian crises due to international conflicts and mapping patterns of global solidarity formed through grassroots actions. The method used is a descriptive qualitative approach with comparative case studies in three conflict areas: Palestine, Rohingya, and Ukraine. Data was collected through literature studies, digital content analysis, and visualization of civil society participation trends from 2015 to 2025. The results show that civil society plays a role not only as a provider of aid, but also as a catalyst for transnational solidarity through digital advocacy, human rights campaigns, and public diplomacy. The solidarity formed is adaptive and contextual, but collectively exhibits a strong cross-border network pattern. Another important finding is the shift in civil society strategies from a traditional aid-based model towards a participatory, digital-transnational model, and finally to an inclusive model that is sustainability-oriented. This research reinforces the argument that civil society is a key element in the architecture of a global humanitarian response that is just and responsive.